Identification of Best Education Management Practices to Improve Learning Outcomes of Muslim Youth Adapting to 21st Century Competition - Lubis, M. Syukri Azwar; Damayanto, Antono; Bangkara, B.M.A.S. Anaconda; Fatoni, M. Anton; Suherlan, Herlan (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study examines the best educational management in the era of information technology, known as the 21st century. This study is qualitative research. Madrasahs in Sambas Regency and as primary data are principals and students. Meanwhile, secondary data consists of articles, books, and other supporting documents in this research. The findings of this study indicate that the best practice model to achieve effective and productive educational goals starts with effective schools, management, strong leadership, clear vision, ability to create a good learning climate, has a student monitoring mechanism, progress to have expectations, high level, supported by resource teachers and also involving the community. The results of this study can later contribute to education in Indonesia in general.